In Vivo Wound Healing Potential of Taro Leaf Extract (Colocasia esculenta L.) Emulgel on Diabetic Rat Models - Erni Rustiani; Lia Suliawati; Sara Nurmala (FITOFARMAKA: Jurnal Ilmiah Farmasi, 2022)
Diabetic wounds are one of the complications of Diabetes Mellitus (DM), which are at risk of infection and can end in amputation. Colocasia leaves contain metabolites of alkaloids, flavonoids, tannins, steroids and saponins, which have antibacterial and antioxidant activity and can accelerate wound healing by helping cell regeneration. This study aimed to determine the effectiveness of taro leaves extract emulgel worked for wound healing in diabetic rats. The test animals were 25 white male rats divided into five groups, namely positive control (applied with Cutimed® gel), negative control (applied with emulgel base), standard control (non-diabetic rats), Treatment-1 (applied emulgel once a day) and Treatment-2 (applied emulgel twice a day). Male white rats were injected with alloxan to make them diabetic and, additionally, given a grade 2 incision. Visual observations started from day 1 to day 16. The results of statistical analysis for measuring the diameter of the incision (Morton's method) and visual observation of the wound (method of scoring) obtained sig α 0.05, meaning that the treatment groups 1 and 2 were significantly different from the negative control. Treatment-2 produced nearly the same effect as the positive control. The conclusion was that 5% Taro Leaf extract emulgel applied twice daily was the most effective in healing cuts in diabetic rats for 13 days.